The effect of educational intervention based on the theory of planned behavior aimed at mothers on osteoporosis prevention behaviors in lower secondary school female students - Fatemeh Shahmohamadi; Meimanat Hoseini; Mahsa Matbouei; Malihe Nasiri (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Osteoporosis is mainly characterized by a low bone mineral density and a sharp architectural and biomechanical deterioration in bone tissue required to maintain bone homeostasis. The theory of planned behavior (TPB) can be considered as one of the leading theories when designing an evidence-based intervention. This study was carried out based on the TPB to determine the effect of an educational intervention aimed at mothers on the prevention of osteoporosis in female students. MATERIALS AND METHODS: A total of seventy mothers of lower secondary school students in Tehran, Iran, participated in this experimental study which was conducted in 2019-2020. The participants were randomly assigned to two groups, namely experimental and control groups. Based on the TPB, a demographic and a researcher-made questionnaire consisting of five sections were used in order to collect data. The validity and reliability of the questionnaires were confirmed before data collection. Four 45-60 min training programs were delivered to the subjects using the TPB. Data were collected before, immediately after, and 1 month following the training program. Finally, IBM SPSS Statistics 21 was used for statistical analysis. RESULTS: No significant difference was observed in terms of attitude, subjective norms, perceived behavioral control, behavioral intention, and osteoporosis prevention-related behavior between the experimental and control groups before proceeding with the intervention (P > 0.05). However, the mean scores of attitude, subjective norms, perceived behavioral control, behavioral intention, and behavior were significantly higher in the experimental group compared to those of the control group following the educational intervention (P < 0.05). CONCLUSION: It can be concluded that such interventions based on the TPB can, in fact, produce a significant effect on osteoporosis prevention-related behaviors. Thus, it can serve as a useful model for planning educational interventions.